High-elasticity waterproof coating and preparation method thereof

By introducing specific monomers and additives into acrylic waterproof coatings, cross-linking and curing at room temperature is promoted, and the problem of slow curing speed of existing coatings under low temperature conditions is solved, and the rapid curing and efficient construction of the coatings are achieved.

CN119875413APending Publication Date: 2025-04-25GUANGDE HAOYU NEW MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510172999.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing acrylic waterproof coatings have slow curing speed under low temperature conditions, resulting in low construction efficiency and long curing time, which limits the expansion of its application fields.

Method used

By introducing N-hydroxymethylacrylamide and bisacetone acrylamide into the acrylic emulsion, combining gluconolactone and gelatin, a crosslinking effect is formed, which promotes crosslinking and curing at room temperature and increases the curing rate.

Benefits of technology

It realizes rapid curing of acrylic waterproof coatings at room temperature, shortens curing time, improves construction efficiency, and expands its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005274591290000081
    Figure BDA0005274591290000081
  • Figure BDA0005274591290000091
    Figure BDA0005274591290000091
  • Figure BDA0005274591290000101
    Figure BDA0005274591290000101
Patent Text Reader

Abstract

The invention discloses a high-elasticity waterproof coating, and belongs to the technical field of coatings. Comprising the following raw materials in parts by weight: 50 to 60 parts of acrylic emulsion, 0.2 to 0.96 part of N-hydroxymethyl acrylamide, 0.3 to 2.04 parts of diacetone acrylamide, 0.1 to 3.5 parts of adipic dihydrazide, 0.1 to 0.15 part of preservative, 20 to 40 parts of inorganic filler, 0.5 to 2 parts of defoaming agent, 5 to 12 parts of gelatin, 0.3 to 0.48 part of glycerol, 0.1 to 0.36 part of natural fiber, 2 to 4.8 parts of glucolactone and 1 to 5 parts of coupling agent. Natural fiber is added to accelerate evaporation of water, gelatin inhibits freezing of water, and drying of the coating is accelerated; gluconolactone is hydrolyzed to reduce the pH value of the system, monomers containing active groups are crosslinked under acidic catalysis to form a three-dimensional network structure, and the coating is rapidly cured at room temperature to endow a coating film with elasticity and water resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a high-elasticity waterproof coating and a preparation method thereof. Background Art

[0002] Waterproof coatings are an indispensable part of modern home decoration and construction. They not only prevent water penetration and protect building structures, but also improve the comfort and durability of the home.

[0003] Acrylic waterproof coating is a single-component, environmentally friendly elastic waterproof coating. It is often used in home waterproofing projects because of its convenient construction, good coating performance, excellent aging resistance and moderate price. The coating is made of modified acrylic ester multi-polymer emulsion as the base material, with a variety of fillers and additives added. It is scientifically processed and can form a waterproof membrane after curing. Its elastic waterproof membrane and the base layer will form a complete waterproof system that combines rigidity and flexibility to adapt to various deformations of the structure and achieve long-term waterproof and anti-seepage effects. In addition, acrylic waterproof coating has strong resistance to high and low temperatures, corrosion resistance, good adhesion and high elongation.

[0004] In the prior art, waterproof coatings are divided into reaction-curing type and volatile type according to the curing method, and acrylic waterproof coatings belong to volatile coatings. Suitable engineering construction conditions for acrylic coatings are environmental humidity below 75% and temperature of 10-35°C. The film-forming process of acrylic coatings depends on the volatilization of water and chemical reactions. When the temperature is below 5°C, the volatilization rate of water slows down and the chemical reaction rate decreases, making it difficult for the coating to cure normally and the coating quality difficult to guarantee; and even if it is cured at room temperature of 10-35°C, it takes about 24 hours to fully cure, which means a long curing time and low construction efficiency; therefore, acrylic waterproof coatings are limited by construction conditions and curing time, and its application field is difficult to expand. Summary of the invention

[0005] The purpose of the present invention is to provide a high-elasticity waterproof coating and a preparation method thereof, so as to improve the room temperature curing rate of the high-elasticity acrylic waterproof coating.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The present invention provides a high elastic waterproof coating, which comprises the following raw materials in parts by mass:

[0008] 50-60 parts of acrylic emulsion, 0.2-0.96 parts of N-hydroxymethyl acrylamide, 0.3-2.04 parts of diacetone acrylamide, 0.1-3.5 parts of adipoyl dihydrazide, 0.1-0.15 parts of preservative, 20-40 parts of inorganic filler, 0.5-2 parts of defoaming agent, 5-12 parts of gelatin, 0.3-0.48 parts of glycerol, 0.1-0.36 parts of natural fiber, 2-4.8 parts of gluconolactone, and 1-5 parts of coupling agent.

[0009] The soft monomer N-hydroxymethyl acrylamide is introduced into the acrylic emulsion, which has a low glass transition temperature. This allows the coating to maintain good flexibility at low temperatures, thereby improving the flexibility and bending resistance of the coating. It can also promote the ductility during the film-forming process, making the surface after film formation smoother and having better appearance and performance.

[0010] Gelatin is a safe, non-toxic and inexpensive natural protein material. Its molecules contain a certain amount of active amino groups that can react chemically with active ketone carbonyl groups. Due to the addition of the monomer diacetone acrylamide in the coating, cross-linking can be formed between gelatin at room temperature. Due to the gelling properties of gelatin in the solution, during the low-temperature freezing process, it can inhibit the aggregation and growth of ice crystals by forming a gel with a network structure. This ability to inhibit the growth of ice crystals helps to improve the material's frost resistance.

[0011] Glycerol has certain plasticizing properties, which can promote gelatin to form a more ordered spatial structure and adjust the viscosity and fluidity of the coating.

[0012] Gluconolactone is a compound produced by the oxidation of glucose. It will slowly hydrolyze into a balanced mixture of gluconic acid and lactone in aqueous solution. The active carbonyl (ketone) and hydrazide groups in the coating will undergo a dehydration reaction under acidic catalytic conditions, thereby achieving room temperature cross-linking and curing. The gluconic acid formed by the hydrolysis of gluconolactone will promote the cross-linking and curing reaction, accelerate the curing rate, and promote gelatin to form a gel under acidic conditions.

[0013] Furthermore, the total mass of the N-hydroxymethyl acrylamide and diacetone acrylamide is 1%-5% of the mass of the acrylic emulsion.

[0014] N-hydroxymethyl acrylamide contains double bonds and hydroxymethyl active groups, and diacetone acrylamide contains ketone active groups. Both can promote cross-linking reactions. Appropriate addition is beneficial to accelerate the curing of the coating.

[0015] Furthermore, the molar ratio of adipoyl dihydrazide to diacetone acrylamide in the raw material is 1:0.6-3 based on the molar ratio of hydrazide group to ketone group.

[0016] Diacetone acrylamide can undergo a cross-linking reaction with adipoyl dihydrazide, achieving self-cross-linking curing at room temperature, and can achieve rapid film formation of the coating at a lower temperature. The molar ratio of hydrazide groups to ketone groups will affect the degree of cross-linking. The higher the degree of cross-linking, the greater the impact strength and the improved performance.

[0017] Furthermore, the preservative is at least one of 1,2-benzisothiazolin-3-one and isothiazolinone, which can effectively inhibit the growth of microorganisms, thereby preventing the corrosion of the coating by bacteria, fungi and other microorganisms in the coating;

[0018] Furthermore, the inorganic filler comprises, by weight: 6.7-13 parts of titanium dioxide, 10-15 parts of heavy calcium carbonate, and 3.3-12 parts of nano zinc oxide.

[0019] On the one hand, adding nano zinc oxide to the paint can improve the corrosion resistance and anti-corrosion properties. Zinc oxide nanoparticles have excellent photocatalytic properties, can degrade harmful substances and inhibit the growth of microorganisms. On the other hand, the addition of zinc oxide can improve the mechanical properties and wear resistance of acrylic paint. Zinc oxide has good anti-ultraviolet properties, can effectively shield the destructive effects of ultraviolet rays on the coating, and improve the durability of the coating.

[0020] Furthermore, the defoaming agent is at least one of an organic silicon defoaming agent and a polyether-modified silicone oil.

[0021] Furthermore, the natural fiber is at least one of coconut shell fiber and bamboo fiber.

[0022] Coconut shell fiber and bamboo fiber are natural fiber materials with a hollow thin-walled multi-tube structure, which gives them a significant capillary effect and excellent moisture transmission function, which helps the paint volatilize moisture at room temperature and promotes the curing of the paint. Coconut shell fiber and bamboo fiber have natural antibacterial and anti-mildew properties, which can inhibit the growth of coating microorganisms.

[0023] Furthermore, the diameter of the natural fiber is 30-50 μm and the length is 0.2-0.3 mm. Selecting natural fibers with smaller diameter and length can avoid the exposure of the fibers on the coating and ensure the flatness of the coating surface.

[0024] Furthermore, the coupling agent is at least one of vinyl triethoxysilane, KH-570 silane coupling agent and titanate coupling agent. Adding the coupling agent can form a stable chemical bond between the inorganic material and the organic polymer, which improves the bonding strength of the interface, can significantly improve the adhesion of the acrylic coating, and can significantly improve the dispersibility of the inorganic filler in the acrylic coating, improve the weather resistance and durability of the coating, thereby enhancing the overall performance of the coating.

[0025] The present invention also provides a method for preparing a high-elastic waterproof coating, comprising the following steps:

[0026] Step 1: Mix acrylic emulsion, N-hydroxymethyl acrylamide, diacetone acrylamide and adipoyl dihydrazide, stir and heat to 50-60° C., add gluconolactone, stir and react for 1-2 hours, and obtain a reaction solution after the reaction is completed;

[0027] Step 2: Mix the inorganic filler and the natural fiber, put the mixture into the reaction solution, add the coupling agent, and stir for 20-30 minutes to obtain a mixed slurry;

[0028] Step 3: Add preservatives, defoaming agents, gelatin and glycerin into the mixed slurry, and stir evenly to obtain a waterproof coating.

[0029] Beneficial effects of the present invention:

[0030] The curing process of water-based acrylic emulsion includes physical drying stage and chemical crosslinking reaction stage. In the physical drying stage, water evaporates. After the water gradually evaporates, the emulsion particles contact and soften, and are bonded into a preliminary film through van der Waals force. In this stage, the addition of natural fiber can accelerate the evaporation of water, and the addition of gelatin can inhibit the freezing of water at low temperature, indirectly affecting the evaporation of water at low temperature and accelerating the process of physical drying stage. In the chemical crosslinking reaction stage, the active groups such as hydroxymethyl, ketone, double bond, hydrazide and amino groups will undergo dehydration condensation reaction to form crosslinking. After the crosslinking reaction is completed, a highly crosslinked three-dimensional network structure is formed inside the coating film, giving the coating film high mechanical strength and water resistance. During the hydrolysis of gluconolactone, as the pH of the system decreases, N-hydroxymethyl acrylamide, diacetone acrylamide, adipic acid dihydrazide and gelatin containing active groups will catalyze the dehydration reaction under acidic conditions and form crosslinks at room temperature. The above process of promoting room temperature crosslinking realizes the rapid curing of the coating at room temperature. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] This embodiment provides a high elastic waterproof coating, which includes the following raw materials by weight:

[0034] 50 parts of acrylic emulsion, 0.2 parts of N-hydroxymethyl acrylamide, 0.3 parts of diacetone acrylamide, 0.5 parts of adipoyl dihydrazide, 0.1 parts of 1,2-benzisothiazolin-3-one, 6.7 parts of titanium dioxide, 10 parts of heavy calcium carbonate, 3.3 parts of nano zinc oxide, 0.5 parts of silicone defoamer, 2 parts of gelatin, 0.3 parts of glycerol, 0.1 parts of coconut shell fiber (diameter 30-50μm, length 0.2-0.3mm), 2 parts of gluconolactone, and 1 part of vinyltriethoxysilane.

[0035] The preparation steps are as follows:

[0036] Step 1: Mix acrylic emulsion, N-hydroxymethyl acrylamide, diacetone acrylamide and adipoyl dihydrazide, stir and heat to 60° C., add gluconolactone, stir and react for 1.5 hours, and obtain a reaction solution after the reaction is completed;

[0037] Step 2: titanium dioxide, heavy calcium carbonate, nano zinc oxide and coconut shell fiber are mixed, the mixture is put into the reaction solution, and vinyl triethoxysilane is added, and the mixture is stirred for 30 minutes to obtain a mixed slurry;

[0038] Step 3: Add 1,2-benzisothiazolin-3-one, silicone defoamer, gelatin and glycerin into the mixed slurry, stir evenly to obtain a waterproof coating.

[0039] Example 2

[0040] The only difference from Example 1 is that the mass fraction of N-hydroxymethyl acrylamide in the raw material is adjusted to 0.5 parts, and the other conditions and steps are the same as Example 1.

[0041] Example 3

[0042] The only difference from Example 1 is that the mass fraction of N-hydroxymethyl acrylamide in the raw material is adjusted to 0.8 parts, and the other conditions and steps are the same as Example 1.

[0043] Example 4

[0044] The only difference from Example 2 is that the mass fraction of adipoyl dihydrazide in the raw material is adjusted to 0.15 parts according to the molar ratio of hydrazide group to keto group of 1:2. Other conditions and steps are the same as those in Example 2.

[0045] Example 5

[0046] The only difference from Example 2 is that the mass fraction of adipoyl dihydrazide in the raw material is adjusted to 0.1 parts according to the molar ratio of hydrazide group to keto group of 1:3, and the other conditions and steps are the same as those in Example 2.

[0047] Example 6

[0048] The only difference from Example 4 is that the total mass of N-hydroxymethyl acrylamide and diacetone acrylamide is 3% of the mass of the acrylic emulsion, the mass fraction of diacetone acrylamide in the raw material is adjusted to 1 part, and the mass fraction of adipic dihydrazide in the raw material is adjusted to 0.5 part according to the molar ratio of hydrazide group to ketone group of 1:2. Other conditions and steps are the same as those in Example 4.

[0049] Example 7

[0050] The only difference from Example 4 is that the total mass of N-hydroxymethyl acrylamide and diacetone acrylamide is 5% of the mass of the acrylic emulsion, the mass fraction of diacetone acrylamide in the raw material is adjusted to 2 parts, and the mass fraction of adipic dihydrazide in the raw material is adjusted to 1 part according to the molar ratio of hydrazide group to ketone group of 1:2. Other conditions and steps are the same as those in Example 4.

[0051] Example 8

[0052] The only difference from Example 6 is that the mass fraction of gelatin in the raw material is adjusted to 8 parts, and the other conditions and steps are the same as Example 6.

[0053] Example 9

[0054] The only difference from Example 6 is that the mass fraction of gelatin in the raw material is adjusted to 10 parts, and the other conditions and steps are the same as Example 6.

[0055] Example 10

[0056] The only difference from Example 8 is that the mass fraction of coconut shell fiber in the raw material is adjusted to 0.2 parts, and the other conditions and steps are the same as Example 8.

[0057] Embodiment 11

[0058] The only difference from Example 8 is that the mass fraction of coconut shell fiber in the raw material is adjusted to 0.3 parts, and the other conditions and steps are the same as Example 8.

[0059] Example 12

[0060] The only difference from Example 10 is that the mass fraction of gluconolactone in the raw material is adjusted to 3 parts, and the other conditions and steps are the same as Example 10.

[0061] Embodiment 13

[0062] The only difference from Example 10 is that the mass fraction of gluconolactone in the raw material is adjusted to 4 parts, and the other conditions and steps are the same as Example 10.

[0063] Examples 14-15

[0064] The only difference from Example 12 is that the mass fractions of the raw materials are different. The other steps and conditions are the same as Example 12. The specific mass fractions are shown in Table 1.

[0065] Table 1

[0066] raw material Embodiment 14 Embodiment 15 Acrylic Emulsion 55 servings 60 servings N-Hydroxymethyl acrylamide 0.55 serving 0.6 parts Diacetone acrylamide 1.1 serving 1.2 servings Adipoyl dihydrazide 0.6 parts 0.6 parts preservative 0.13 parts of isothiazolinone 0.15 parts of isothiazolinone Titanium dioxide 10 servings 13 servings Heavy calcium carbonate 10 servings 15 servings Nano zinc oxide 10 servings 12 servings Defoaming agent 1 part polyether modified silicone oil 2 parts of polyether modified silicone oil gelatin 8.8 servings 9.6 servings glycerin 0.4 parts 0.48 Natural Fibers Bamboo fiber 0.22 parts 0.24 Gluconolactone 3.3 servings 3.6 servings Vinyltriethoxysilane 3 servings 5 servings

[0067] Comparative Example 1

[0068] Compared with Example 1, gelatin is not added to the raw materials of the coating in this comparative example, and other conditions and steps are the same as Example 1.

[0069] Comparative Example 2

[0070] Compared with Example 1, natural fiber is not added to the raw materials of the coating in this comparative example, and other conditions and steps are the same as Example 1.

[0071] Comparative Example 3

[0072] Compared with Example 1, gluconolactone is not added to the raw materials of the coating in this comparative example, and other conditions and steps are the same as those in Example 1.

[0073] The coatings prepared in Examples 1 to 15 and Comparative Examples 1 to 3 were tested for performance, and the results are shown in Table 2.

[0074] The performance test refers to the "JCT 864-2023 Polymer Emulsion Building Waterproof Coating" standard.

[0075] Table 2

[0076]

[0077]

[0078]

[0079] As can be seen from Table 1, the amount of N-hydroxymethyl acrylamide introduced into the raw materials in Examples 1 to 3 increases, and its tensile strength and elongation at break are higher. When N-hydroxymethyl acrylamide is excessive, its bonding strength will decrease. In the results of Examples 4 and 5, its curing time is shorter. In Examples 8 and 9, increasing the proportion of gelatin can improve the elastic properties of the coating and promote cross-linking curing. In Examples 10 and 11, coconut shell fiber can significantly shorten the surface drying time and increase the elongation at break due to the water transmission in the coating and the fiber winding nanoparticle function. The coating rubber comparative example prepared in the embodiment of the present invention has a short curing film-forming time, and the tensile strength and elongation at break indexes after film formation are high, and has good elasticity and waterproofness.

[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly elastic waterproof coating, characterized in that: The following raw materials are included by weight: 50-60 parts of acrylic emulsion, 0.2-0.96 parts of N-hydroxymethyl acrylamide, 0.3-2.04 parts of diacetone acrylamide, 0.1-3.5 parts of adipoyl dihydrazide, 0.1-0.15 parts of preservative, 20-40 parts of inorganic filler, 0.5-2 parts of defoaming agent, 5-12 parts of gelatin, 0.3-0.48 parts of glycerol, 0.1-0.36 parts of natural fiber, 2-4.8 parts of gluconolactone, and 1-5 parts of coupling agent.

2. A highly elastic waterproof coating according to claim 1, characterized in that: The total mass of the N-hydroxymethyl acrylamide and diacetone acrylamide is 1%-5% of the mass of the acrylic emulsion.

3. A highly elastic waterproof coating according to claim 1, characterized in that: The ratio of diacetone acrylamide and adipoyl dihydrazide in the raw materials is 1:0.6-3 according to the molar ratio of hydrazide group to ketone group.

4. A highly elastic waterproof coating according to claim 1, characterized in that: The preservative is at least one of 1,2-benzisothiazolin-3-one and isothiazolinone.

5. The high elastic waterproof coating according to claim 1, characterized in that: The inorganic filler comprises, by weight, 6.7-13 parts of titanium dioxide, 10-15 parts of heavy calcium carbonate, and 3.3-12 parts of nano zinc oxide.

6. A highly elastic waterproof coating according to claim 1, characterized in that: The defoamer is at least one of an organic silicon defoamer and a polyether modified silicone oil.

7. The high elastic waterproof coating according to claim 1, characterized in that: The natural fiber is at least one of coconut shell fiber and bamboo fiber.

8. The high elastic waterproof coating according to claim 1, characterized in that: The natural fiber has a diameter of 30-50 μm and a length of 0.2-0.3 mm.

9. The high elastic waterproof coating according to claim 1, characterized in that: The coupling agent is at least one of vinyl triethoxysilane, KH-570 silane coupling agent and titanate coupling agent.

10. A method for preparing a highly elastic waterproof coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Mix acrylic emulsion, N-hydroxymethyl acrylamide, diacetone acrylamide and adipoyl dihydrazide, stir and heat to 50-60° C., add gluconolactone, stir and react for 1-2 hours, and obtain a reaction solution after the reaction is completed; Step 2: Mix the inorganic filler and the natural fiber, put the mixture into the reaction solution, add the coupling agent, and stir for 20-30 minutes to obtain a mixed slurry; Step 3: Add preservatives, defoaming agents, gelatin and glycerin into the mixed slurry, and stir evenly to obtain a waterproof coating.

Citation Information

Cited By

  • High-elasticity waterproof emulsion and preparation method thereof

    CN120818273A

  • High-elastic waterproof emulsion and preparation method thereof

    CN120818273B